Sustainable development goals (SDG) and its intersection with health and well-being - Poddar, Sandeep; Ansar, Waliza (IGI Global Scientific Publishing, 2025)
"This book will explore the economic, environmental, healthcare and social facets of sustainable development, delving into its many components"-- Provided by publisher.
Keywords: Sustainable development.; Environmental health.; Toxicology.; Environmental toxicology.; Toxicology -- Environmental aspects.; elektronické knihy; electronic books